(untitled) (Global Journal of Medical Research, 2014)
Osteoarthritis is a common orthopedic problem in the small animals patients. In most cases, the degenerative changes in the joint are secondary to some predisposing cause. The objective of this case study was to assess Diagnostic Value of Histopathology Radiography and Computed Tomography for Diagnosis of Canine Osteo-arthritis The study was conducted in Police Dogs Administration (Ministry of Interior, X-ray Department), included Female German Shepherd dog which diagnosed radiographically for hip dysplasia and osteoarthritis. Using conventional radiography and CT images It concluded that conventional radiography is the most common method used to evaluate osteoarthritis, there has been an increase in the application of other imaging technologies (CT) during the past several years. These modalities and thehistopathology can provide the clinician with additional information that can improve case management.